The 5A/6A promoter polymorphism of matrix metalloproteinase 3 (MMP-3) gene in menopausal women with ovarian cancer - Kulig, Andrzej; Smolarz, Beata; Kozłowska, Elżbieta; Romanowicz-Makowska, Hanna; Szyłło, Krzysztof; Niewiadomski, Mariusz; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2002)
Background: Matrix metalloproteinases (MMPs) comprise family proteolytic enzymes that degrade of extracellular matrix components and therefore play an important role in tumour cell invasion and cancer metastasis. Overexpression of matrix metalloproteinase 3 (MMP-3 or stromelysin 1) gene has been demonstrated in various types of cancers and high level of MMP-3 protein in tumour is a poor prognostic factor for patients. The insertion (6A)/deletion (5A) polymorphism (5A/6A polymorphism) located at the promoter of the MMP-3 gene may have functional significance in the regulation of its expression. Materials and methods: In the present work the distribution of genotypes and frequencies of alleles of the 5A/6A polymorphism in subjects with ovarian cancer were investigated. Paraffin embedded tumour tissues were obtained from 50 menopausal women with ovarian cancer. The 5A/6A polymorphism were determined by PCR amplification using the allele specific primers. Results: The distribution of the genotypes of the 5A/6A polymorphism in both control and patients did not differ significantly (p>0.05) from those predicted by the Hardy-Weinberg distribution. Additionally, there were no significant differences (p >0.05) in genotype distributions and allele frequencies between subgroups assigned to histological stage. Conclusion: The results suggest that the 5A/6A polymorphism of MMP-3 gene may not be linked with appearance and development of ovarian cancer but further research, conducted on larger population, are needed to clarify this point.